Mechanistic Understanding of Nitrogen Behaviour in Floating Treatment Wetlands: Abatement of Ammonia Flux. Issue 1 (June 2021) - Al Lami, Muwafaq H.; Whelan, Mick J.; Boom, Arnoud; Harper, David M.
Abstract: Nitrogen behaviour in domestic wastewater was investigated to develop a mechanistic understanding of ammonia dynamics in Floating Treatment Wetlands (FTWs) and to improve design and operation. A critical FTW design (full coverage of the floating mat and maximum plant density) was evaluated to optimize treatment performance of a pilot-scale system in removing ammonia under different operational volumes. A system dynamics approach as a framework was employed for robust understanding of the treatment mechanisms and system performance in removing ammonia. The results revealed that ammonia removal was enhanced in FTWs and the magnitude of removal was controlled by the design examined. Findings suggest that a design code of full coverage of water surface with mat material, high plant density, and low water volume can be considered as a critical design for FTW system to remove ammonia from domestic wastewater. This design promoted nitrification as principal ammonia removal process even when plants were present. The contribution of nitrification to overall ammonia removal was estimated to be between 81 and 85%. Plant uptake contributed to 14-19% of the total N loss. Ammonia loss via volatilization was determined to be negligible in examined system. Kinetics parameters for ammonia removal were between 0.14-0.22 day -1 in FTWs compared to 0.01-0.02 day -1 in controls. Understanding the contribution of removal processes of N could be useful to improve treatment system design, and enhance treatment performance.